A new species of Steneotarsonemus (Acari: Tarsonemidae) from common reed grass, Phragmites australis (Poaceae) in the wetlands of Eastern India - Mondal, Priyankar; Ganguly, Moumi; Karmakar, Krishna; Lofego, Antonio C. [UNESP]; Moraes, Gilberto J. de (Taylor & Francis Inc, 2021)
A new species of tarsonemid mite, Steneotarsonemus indianensis sp. nov., is described from common reed grass Phragmites australis (Poaceae). This new species is the first species described under the genus Steneotarsonemus from Eastern India and the sixth species of the subgenus Steneotarsonemoides worldwide. Keys to the world species of Steneotarsonemoides are provided.
Keywords: Steneotarsonemus; Taxonomy; keys; reed grass